Prinsip Perlindungan Hukum Terhadap Korban Kekerasan Dalam Rumah Tangga Berdasarkan Undang -Undang Nomor 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga - Bachtiar, Moch. Yusuf; Abadi, Suwarno (Universitas Wijaya Putra, 2024)
Domestic violence (DV) represents a significant legal issue in Indonesia. Indonesia has enacted legislation, namely Law Number 23 Year 2004 on the Elimination of Domestic Violence, with the objective of providing protection for victims of domestic violence. In recent times, there has been a shift towards a restorative justice and penal mediation-based approach to resolving domestic violence cases. This article will examine the legal protection of victims of domestic violence in accordance with the aforementioned legislation, as well as the settlement of domestic violence cases through penal mediation at Surabaya Police Station. This is legal research with statute and conceptual approach. The results revealed that the legal protection granted to victims of domestic violence through Law Number 23 Year 2004 on the Elimination of Domestic Violence encompasses three forms of protection are as follows: 1.) external protection, 2.) legal protection through repressive action and 3.) curative protection. Criminal acts of domestic violence are settled through penal mediation and restoratife justice at the Surabaya Police Station. Currently, two criminal offence settlements are based on the National Police Chief Regulation. It is recommended that penal mediation and restorative justice be regulated in the form of rules in the form of laws in the future.